2005
DOI: 10.1103/physrevc.72.045503
|View full text |Cite
|
Sign up to set email alerts
|

Time-reversal-violating Schiff moment ofHg199

Abstract: We calculate the Schiff moment of the nucleus 199 Hg, created by πNN vertices that are odd under parity (P) and time-reversal (T). Our approach, formulated in diagrammatic perturbation theory with important core-polarization diagrams summed to all orders, gives a close approximation to the expectation value of the Schiff operator in the odd-A Hartree-Fock-Bogoliubov ground state generated by a Skyrme interaction and a weak P-and T-odd pion-exchange potential. To assess the uncertainty in the results, we carry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
94
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 32 publications
(45 reference statements)
6
94
0
Order By: Relevance
“…[67] and does not take into account the recent computations of refs. [68,69]. The latter two computations give an enhanced sensitivity of the nuclear Schiff moment of 199 Hg to the isoscalar, T-and P-odd pion-nucleon coupling,ḡ (0) π as compared to ref.…”
Section: Jhep08(2010)062mentioning
confidence: 84%
“…[67] and does not take into account the recent computations of refs. [68,69]. The latter two computations give an enhanced sensitivity of the nuclear Schiff moment of 199 Hg to the isoscalar, T-and P-odd pion-nucleon coupling,ḡ (0) π as compared to ref.…”
Section: Jhep08(2010)062mentioning
confidence: 84%
“…[79][80][81]), the dependence of S A onḡ 0,1 is far more uncertain due to the complicated nuclear many-body problem [82,83] (for a detailed discussion, see ref. [84]).…”
Section: Jhep02(2016)011mentioning
confidence: 99%
“…[36] found that theḡ 1 coefficient is very sensitive to the model-dependent nuclear potential inputs and may be suppressed by an order of magnitude (or more) and may have opposite sign compared to Refs. [59,60]. These nuclear physics uncertainties are crucial for constraining D t using d Hg .…”
Section: B Electric Dipole Momentsmentioning
confidence: 99%
“…Second, the Schiff moment is computed in terms of P, T -odd nucleon-pion couplings, of which only the isovector couplinḡ g 1 is relevant since O LR is isovector [58]. Previous nuclear computations found (keeping onlȳ g 1 terms): S Hg = −0.071 gḡ 1 e cm 3 [59] and S Hg = −0.055 gḡ 1 e cm 3 [60], where g ≈ 13.5 is the (CP-even) pion-nucleon strong coupling. However, a recent and improved computation by Ref.…”
Section: B Electric Dipole Momentsmentioning
confidence: 99%